DEVELOPMENT OF CHILDREN OF CHILDREN'S LANGUAGE BY TIME - Suaad Yaseen Khalaf (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Language acquisition is the activity required to understand the language, also, production of the words and sentences that are used for communication. My paper includes the language acquired by children without learning grammatical rules. Developing Children's language moved from simple form to complex. The language begins by using simple words without meaning. By time; the child acquired new words that have meaning for forming more complex sentences used for connections with the other. Gradually, the sentences and the words are united together to form logical meaning. Language development is a complex process by which children can understand and communicate language during their early childhood. The first language or mother language was gotten firstly at the early stage of the life called sometimes the native language, while the second language can be learned at adulthood as an additional language. The development of language is making the child understand the word meaning for communication with the other people to express feelings and the events. The language supports problem-solving, thinking, maintaining relationships, and problem simplification. The development of the language is related to the emergence of language and linguistics.